Leveraging census data to design and implement an area-based deprivation index to assess health inequalities in Ecuador - Andrade, Diego; Dundas, Ruth; Olsen, Jonathan; Chis Ster, Irina; Project, SEDHI (International Journal of Population Data Science, 2026)
Introduction Deprivation measures have been used in research to assess within-country health inequalities globally. Most of these indices are created using data from national census, given their availability and nationwide coverage. Objectives This study aims to create a census-based deprivation index in Ecuador, the Ecuadorian Deprivation Index (EDI), that reflects the country specific context using national census data for four geographical units (census sector, parish, canton and province). It will be compared to two traditional small area indices (Townsend and Carstairs) to assess the most appropriate and context specific index for Ecuador. Finally, the performance of the three indices will be assessed by examining the association and extent of inequalities with teenage pregnancy as this has been shown to be socially patterned in other countries. Methods This study uses the 2010 Ecuadorian census and follows the stages and recommendations for developing small-area deprivation indices. The Townsend and Carstairs are firstly replicated. For the EDI, Principal Component Analysis is used to select the most appropriate indicators. Summary measures for higher-level geographical areas were developed following the techniques used in the English Index of Multiple Deprivation. Inequalities in teenage pregnancy is measured using the Slope index of inequality and the Relative index of inequality. Results The three indices exhibit a good match in urban areas and can describe pattern of inequalities in teenage pregnancy. However, the EDI Index captures rural deprivation more appropriately and that includes the Coast and Amazon geographical regions. Conclusions Traditional deprivation measures may not adequately identify deprivation in Ecuador, given the country's unique specific contextual factors. The wider scope of the EDI will inform policy-makers towards developing tailored programs to alleviate deprivation and health inequalities in Ecuador.